(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация. Статья посвящена анализу перспектив цифровизации банковских услуг в Узбекистане с использованием технологий эмиссии и эквайринга. Рассматриваются текущий уровень внедрения цифровых технологий в банковском секторе, их влияние на доступность финансовых услуг, ускорение безналичных расчетов и развитие электронной коммерции. Особое внимание уделяется внедрению инновационных решений, таких как искусственный интеллект, блокчейн и биометрия, а также роли государственной поддержки и международного сотрудничества. В работе предложены рекомендации по повышению эффективности и безопасности цифровых банковских услуг. Abstract. The article focuses on analyzing the prospects for the digitalization of banking services in Uzbekistan through the adoption of issuing and acquiring technologies. It examines the current level of digital technology integration in the banking sector, its impact on financial service accessibility, acceleration of cashless payments, and the development of e-commerce. Special attention is given to the implementation of innovative solutions such as artificial intelligence, blockchain, and biometrics, as well as the role of government support and international collaboration. The study provides recommendations for enhancing the efficiency and security of digital banking services.